Resistance of the Nahdlatul Ulama Party towards the New Order 1967-1969 - Mahmud, Mahmud; Yuliati, Dewi; Alamsyah, Alamsyah (Indonesian Historical Studies, 2023)
This study discusses the resistance of the Nahdlatul Ulama Party (Partai Nadhlatul Ulama/ PNU) towards the New Order government from 1967-1969. This study analyses the process of PNU's resistance to the New Order from 1967-1969. This study uses historical research methods, which consist of four stages of historical research methods, namely: heuristics, source criticism, interpretation and historiography. Using the historical method, this study answers questions regarding the form of PNU's channel of resistance against the New Order and the results achieved against the government during the 1967-1969 period. This study uses the farming community-based resistance theory developed by James Scott. Resistance theory is used to explain the PNU's resistance to the New Order through various existing political channels. The New Order government began to show signs of being anti-democratic by imposing political policies that put pressure on political parties and intervening in the PNU organization's internal realm. PNU's resistance to the New Order government was a reaction to various government interventions and actions that attempted to minimize the role and influence of the PNU. This research resulted in an analysis of PNU's resistance to the New Order, which had a more solid institutional structure through various existing political channels. The PNU's resistance is understood as a self-defence effort against multiple interventions by the government on the PNU's political institutions.